Exploring causes of bribery: A case study in a Public Organization in Malaysia - Sathappan, Malini; Omar, Zoharah; Arif, Ismi; Sathappan, Ramesh (2016)
Purpose: The purpose of the research paper is to explore and understand the causes of bribery among law enforcement officers in Malaysia.